Effectiveness of Think-Pair-Share on active participation of elementary teacher education students - Ronny Mugara; Enjang Yusup Ali (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2026)
Student participation in class discussions in the Elementary School Teacher Education (PGSD) program is often still low, indicating the need for an instructional model that actively engages students. This study aims to examine the effectiveness of the Think-Pair-Share (TPS) learning model in increasing the active participation of PGSD students in class discussions. The study employed a quantitative approach using a quasi-experimental One Group Pretest–Posttest Design involving 35 PGSD students. Data were collected through pretest–posttest instruments and observation sheets of student active participation and analyzed using descriptive statistics, paired sample t-test, and Cohen’s d effect size. The results showed a significant increase in students’ pretest and posttest scores, with a t-statistic of 19.18 and a p-value far below 0.05. The effect size analysis yielded a Cohen’s d value of 3.24, indicating a very strong effect of the TPS model. Observation results also demonstrated an improvement in all indicators of active participation from the fairly active category to very active. In conclusion, the Think-Pair-Share learning model is effective in enhancing active participation and creating a more interactive and collaborative learning environment for PGSD students.